Application of a comprehensive extraction technique for the determination of poly- and perfluoroalkyl substances (PFASs) in Great Lakes Region sediments. (December 2016) - Guo, Rui; Megson, David; Myers, Anne L.; Helm, Paul A.; Marvin, Chris; Crozier, Patrick; Mabury, Scott; Bhavsar, Satyendra P.; Tomy, Gregg; Simcik, Matt; McCarry, Brian; Reiner, Eric J.
Abstract: A comprehensive method to extract perfluoroalkane sulfonic acids (PFSAs), perfluoroalkyl carboxylic acids (PFCAs), polyfluoroalkyl phosphoric acid diesters (diPAPs), perfluoroalkyl phosphinic acids (PFPiAs) and perfluoroalkyl phosphonic acids (PFPAs) from sediment and analysis by liquid chromatography tandem mass spectrometry (LC-MS/MS) was developed and applied to sediment cores from three small isolated lakes (Plastic Lake, Lake 442, Lake Tettegouche) and Lake Ontario in the Great Lakes Region. Recoveries of the target compounds using the optimized acetonitrile/sodium hydroxide extraction ranged from 73% to 120%. The greatest concentrations of per- and polyfluorinated alkyl substances (PFASs) were recorded in sediment from Lake Ontario (ΣPFASs 13.1 ng/g), where perfluorooctane sulfonic acid (PFOS) contributed over 80% of the total. Concentrations in Lake Ontario were approximately 1–2 orders of magnitude greater than the more remote lakes subject to primarily atmospheric inputs. Whilst the PFAS contribution in Lake Ontario was dominated by PFOS, the more remote lakes contained sediment with higher proportions of PFCAs. Trace amounts of emerging PFASs (diPAPs and PFPiAs) were found in very recent surface Lake Ontario and remote lake sediments. Graphical abstract: Highlights: Simultaneous extraction of PFSAs, PFCAs, diPAPs, PFPiAs and PFPAs from sediment. PFAS contribution in Lake Ontario was dominated by PFOS. Remote lakes contained sediment with higher proportions of PFCAs and diPAPs. PFAS concentrations increased with time but proportion of PFOS to ƩPFAS decreased.